ELEVATOR-TYPE PARKING LOTS - Carmen Elisabeta RADU; Edward RĂŞCHITOR; Iosif TEMPEA (Fiabilitate şi Durabilitate, 2018)
The paper deals with the types of automated parking facilities in operation, taking into account the advantages and problems induced by them. There are presented underground parking, one-and two-platform elevators and their mechanisms, as well as robotic parking along with the existing mechatronic system.